Tris–Egg Yolk–Glycerol (TEY) Extender Developed for Freezing Dog Semen is a Good Option to Cryopreserve Bovine Epididymal Sperm Cells. Issue 1 (21st November 2014) - Lopes, G; Soares, L; Ferreira, P; Rocha, A
Contents Cryopreservation of epididymal spermatozoa is often performed after shipping the excised testis–epididymis complexes, under refrigeration, to a specialized laboratory. However, epididymal spermatozoa can be collected immediately after excision of the epididymis and sent extended and refrigerated to a laboratory for cryopreservation. In this experiment, we evaluated the effect of both methods of cold storage bovine epididymal spermatozoa as well as of two different extenders on spermatozoa characteristics after freeze–thawing. For that, spermatozoa collected from the caudae epididymis of 19 bulls were extended and cryopreserved in either AndroMed® or a Tris–egg yolk (TEY)‐based extender. Cryopreservation of sperm cells was performed immediately after castration (Group A, n = 9) or after cold storage for 24 h diluted in the two extenders and (Group B, n = 9) and also after cold storage for 24 h within the whole epididymis (Group C, n = 10). Sperm subjective progressive motility (light microscopy), plasma membrane integrity (hypoosmotic swelling test) and sperm viability (eosin–nigrosin) were evaluated. In vitro fertilization and culture (IVF) was performed to assess the blastocyst rate. No differences (p > 0.05) were observed on post‐thaw sperm parameters between samples from Group A, B and C. TEY extended samples presented a higher (p < 0.01) percentage of progressive motile and live sperm, than those extended in AndroMed®. Blastocyst rate after IVF differed only (p < 0.05) between the reference group (IVF performed with frozen semen with known in vitro fertility) and Group A extended in AndroMed®. We conclude that when cryopreservation facilities are distant from the collection site, bovine epididymal sperm can be shipped chilled overnight either within the epididymal tail or after dilution without deleterious effect on post‐thaw sperm quality. TEY extender was more suitable for cold storage and freezing bovine epididymal sperm, than the commercial extender AndroMed®.